Video-Based Instruction to Boost Students’ Presentation Skill - Dina Rafidiyah; Melly Thania (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2018)
Video-Based Instruction in teaching has been used for long time to boost students’ speaking skill. Presentation, as one of the speaking skills, is considered hard for most of the students, especially for non-English department ones. Therefore, the aim of this study is to know the relationship of video-based instruction and the students’ ability to do presentation, Furthermore, this study is intended t to explore if the video-based instruction can motivate them to learn English more. This is a quantitative research. The questionnaire is administered to gain the data regarding students of pharmacy major about their opinions, responses, and motivations of using video-based instruction in making a presentation. The population of this study is 136 first year students of pharmacy from three classes, and the samples are 20 students for each class. The implication of this study is to equip the students with the skills of using video as a medium for learning English.